Energy Expenditure During Stump Area Operation - Mitra, S. K.; Sood, K. G. (Indian Forester, 1980)
Systematic studies on the physiological aspect of logging has been initiated recently by the logging branch of F.R.I. So far, logging research was restricted in finding out the economic suitability of various tools and equipments and the consequent prediction of productivity. The present persuits economics in logging will bridge the gap and will enable us to identify the suitability of a method or an equipment in a more rational basis. Accordingly study was taken in the high elevation forests in the Chajpur area of Himachal Pradesh with the aim of determining the energy consumption of forest workers in various stump area operation. The study reveals that there is significant reduction in energy expenditure when maintenance of saws are done scientifically. It is observed that during felling and conversion of trees the raker saw (2 : 1) involves consumption of least energy provided the maintenance is done scientifically. Delimbing operation is the most strenuous component of stump area operation and there is scope for improvement of the existing handtools so that physiological workload is reduced.